O ciberespaço e as reconfigurações burocráticas: a experiência atual - Archer, Claudia Maria da Costa (2017)
This thesis analyzes how the reconfiguration of the state's bureaucracy occurred with the introduction of information and communication technologies (ICTs) into the brazilian's Stated. It begins with the contextualization of this moment through the history of "cognitive capitalism" and the "reform of the Brazilian's state of 1995". Because these are two facts that led the Brazilian state to introduce ICT in its bureaucratic routines, reconfiguring them. This change in routines leads state workers to adapt to the introduction of ICT in their work processes. This generates a hierarchy through the various levels of adaptation found in the burearacy. One has, therefore, those bureaucrats who have not adapted and leave the State, whether by retirement, or Programs of voluntary dismissals, they do not feel able to renew their knowledge, or even have no interest. Another type of bureaucrat is one who can‘t adapt, but continues in the public service, but calls on the help of another to help him, creating the micro regulations of power, and delaying the task. This relation it was called by Crozier (1981) of "power of the expert", that the power of the one that knows. Finally, from the categorization of the adapted bureaucrats, they are those who developed the skills necessary to carry out the reconfigured bureaucratic routines. In addition to the adapted bureaucrats, based on Haraway's theory of cyborgs (2000), another category of bureaucrats is identified, those who arrive at the state already inserted in cyberspace, they are the cyberbureaucrats.